Copper/GanPhos-Catalyzed 1,3-Dipolar Cycloaddition of Azomethine Ylides: An Efficient Access to Chiral Pyrrolidine Spirocycles - Gan, Zhenjie; Li, Ke; Zhang, Hui; Li, Er-Qing (Synthesis, 2020)
A highly efficient copper/GanPhos-catalyzed 1,3-dipolar cycloaddition of azomethine ylides is reported. This viable transformation provides a series of optically active spiro[dihydronaphthalene-2,3′-pyrrolidine]s, bearing one spiro quaternary and three tertiary stereogenic centers, in good yields and with high ee values. This protocol features high diastereo- and enantioselectivity, broad substrate scope and mild reaction conditions.
Keywords: pyrrolidine spirocycles; 1,3-dipolar cycloaddition; azomethine ylides; stereogenic centers; copper; GanPhos